EXPERIMENTAL IMPLEMENTATION AND CODE DEVELOPMENT TO EVALUATE A PARABOLIC TROUGH SOLAR THERMAL POWER PLAN - MOHAMMAD, SANAN T. (2018)
The performance of the Parabolic Trough Power Plant (PTPP) is highly dependent on geographic location and meteorological conditions